2018
DOI: 10.1021/acs.est.8b00937
|View full text |Cite
|
Sign up to set email alerts
|

Carbonaceous Nanomaterials Have Higher Effects on Soybean Rhizosphere Prokaryotic Communities During the Reproductive Growth Phase than During Vegetative Growth

Abstract: Carbonaceous nanomaterials (CNMs) can affect agricultural soil prokaryotic communities, but how the effects vary with the crop growth stage is unknown. To investigate this, soybean plants were cultivated in soils amended with 0, 0.1, 100, or 1000 mg kg of carbon black, multiwalled carbon nanotubes (MWCNTs), or graphene. Soil prokaryotic communities were analyzed by Illumina sequencing at day 0 and at the soybean vegetative and reproductive stages. The sequencing data were functionally annotated using the funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 63 publications
1
34
0
1
Order By: Relevance
“…Box plots for significant OTUs were generated using R after Borcard, Gillet, and Legendre (2018). To compare the relative abundances of putative functional bacterial groups between sampling sites or depth intervals, one-way analysis of variance (ANOVA) with a post hoc least significant difference (LSD) test was employed according to Ge et al (2018) using R after Borcard et al (2018).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Box plots for significant OTUs were generated using R after Borcard, Gillet, and Legendre (2018). To compare the relative abundances of putative functional bacterial groups between sampling sites or depth intervals, one-way analysis of variance (ANOVA) with a post hoc least significant difference (LSD) test was employed according to Ge et al (2018) using R after Borcard et al (2018).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The main limitation of applying FAPROTAX to our data is the implicit assumption in FAPROTAX that if the cultured members of a taxon can perform a particular function, then all members of the taxon (both the cultured and non-cultured) can perform that function ( Ge et al, 2018 ). However, less than 1% of all microbial taxa have been studied in culture.…”
Section: Discussionmentioning
confidence: 99%
“…However, less than 1% of all microbial taxa have been studied in culture. In this sense, the functional implications of the shifts in bacterial community could be larger than what can be currently inferred using this approach ( Ge et al, 2018 ). With the 16S sequencing approach, we used function-by-proxy to determine the components of the structure–function relationship; however, our ability to parse functional groups is limited.…”
Section: Discussionmentioning
confidence: 99%
“…A correlation between the reverse dose relationship and the agglomeration state of MWCNTs was previously established. [19] Specifically, MWCNTs negatively affected soybean nodulation and N 2 fixation potential [19] and significantly altered soil prokaryotic communities, [22] with stronger effects observed for lower MWCNT doses.…”
Section: Global Transcriptomic Response Of B Diazoefficiens To Enms mentioning
confidence: 99%
“…Soybean exposure to CeO 2 NPs and MWCNTs via soil resulted in root nodules that were devoid of bacteroids, [19,21] indicating that symbiotic bacteria were perturbed by ENMs. However, Ge et al [22] found that bacterial populations associated with N 2 fixation were insensitive to CNM treatment in soybean-planted soil. Altogether these results suggest that ENM effects on N 2 -fixing systems may not manifest in the growth inhibition of symbiotic bacteria but rather occur during the initiation of nodulation or symbiosis formation.…”
Section: Introductionmentioning
confidence: 99%